Techno-economic and lifecycle assessment of transition towards eco-efficiency energy recovery from brazilian municipal solid waste using integrated trigeneration systems - Thangarasu, Vinoth (Universidade Estadual Paulista (Unesp), 2024)
The municipal solid waste’s sustainable management is necessary because of the environmental and health risks involved, as well as to meet the Sustainable Development Goals and address disposal difficulties with significant amounts of (MSW) generated. Maintaining a balance between consumption and recycling is necessary to control the waste life cycle of MSW. In order to stop the waste loop, methods for thermally degrading MSW that aim to recover energy and produce value-added materials have drawn interest recently. This review sheds light on the present scenario and highlights important prospects and obstacles for the MSW generation and management in Brazil. Gasification is one such promising method. The gasification kinetics of MSW and its individual components are still lacking. A comprehensive understanding of the thermal behavior of MSW and its individual components aids in selecting appropriate kinetic-free models that fit the thermogravimetric data and help optimize the gasification process. Thermogravimetric analysis is a useful tool for measuring the thermal behavior of the sample. This present work extensively reviews the MSW and its components' thermal behavior and kinetic analysis using various iso-conversational or kinetic-free approaches thoroughly examined in different atmospheres. Moreover, this review highlights the limitations of kinetic-free models, and future directions are discussed. This perspective review may help researchers, policymakers, and non-profit organizations involved in MSW management and the waste-to-energy industry in Brazil. Also, an experimental investigation of the gasification kinetics of Brazilian municipal solid waste (MSW) and its components under air, CO2, and air/CO2 (70/30 vol.%) atmospheres was carried out. Paper and plastic ignition indices are 6 and 3 times that of food waste, which are 38.6 × 10-3 %/min3 and 19.6 × 10-3%/min3, respectively, implying a faster separation of volatile compounds from the paper and plastic. The minimum Eα values of 132 kJ/mol and 140 kJ/mol have been obtained for paper waste under air and air/CO2, respectively. On CO2 condition, MSW has an average Ea value of 96 kJ/mol. Under an air/CO2 atmosphere, a high synergistic ∆W of -4.7 wt.% has been identified between individual components. The presence of air and CO2 improves the oxidation and char gasification process, thus resulting in better combustion. Hence, the gasification of MSW under an air/CO2 atmosphere would improve the waste-to-energy plant’s performance and minimize the CO2 emission.
Avaliação tecnoeconômica e do ciclo de vida da transição para a recuperação energética ecoeficiente de resíduos sólidos urbanos brasileiros utilizando sistemas integrados de Trigeração
Keywords: Waste management; Waste-to-energy; Thermogravimetric analysis; Gasification kinetics; Kinetic-free models